Effect of weed management and nitrogen level on nutrient loss and tuber yield of potato (Solanum tuberosum) - JAISWAL, V P (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during autumn 1989 and 1991 to study Ihe effect of levels of nitrogen (80,160 and 240 kg/ha) and weed management on weed infestation, nutrient loss and tuber yield of potato (Solanum tuberosum L.). The weed-control treatments were metribuzin @ 0.75 kg/ha, isoproturon @ 0.75kg/ha. paraquat @ 0.50 kg/ha, 1 weeding + 1 earthing-up and the unweeded control. All the weed-control treatments reduced Ihe weed infestation (33-87%), showing respectively 87, 67. 33 and 76% efficiency compared wilh the control, giving 36.0,34.5,31.2.32.6 and 26.9 tonnes/ha yield. All increase in N level from 80 to 160 and 240 kg/ha increased Ihe tuber yield to 27.5, 33.1 and 36.1 tonnes/ha respectively, without affecting the weed density and dry weight. The uptake by the weeds led to loss in yield of 4-87, 1-10 and 4-82 kg/ha of N, P and K respectively. The loss was maximum in The unweeded control and least under metribuzin treatment.